Forms of Interactive Teaching - Berkinov Alisher Abdurashidovich1 (European Science Publishing, 2024)
Raising a generation with high potential is the most sacred. Therefore, in our country, we must create the necessary conditions and opportunities for raising a healthy and well-rounded generation, realizing the creative and intellectual potential of young people, and raising the young men and women of our country to be fully mature individuals who fully meet the requirements of the 21st century. Large-scale measures are being implemented.
Keywords: Interactive, technology, innovation, alternative, authors, concept.